Economic policy uncertainty and dynamic correlations in energy markets: Assessment and solutions - Wang, Xiong; Li, Jingyao; Ren, Xiaohang; Bu, Ruijun; Jawadi, Fredj (Energy economics, 2023)
The objective of this study is twofold. On the one hand, we investigate the dynamic correlations among the energy, clean energy, crude oil, and carbon markets using a DCC-MIDAS specification. On the other hand, we check whether the Economic Policy Uncertainty (EPU) has had an impact on the cross-asset correlations under different market conditions using the Quantile-on-Quantile (QQ) technique. Further, we comparatively compare the hedging potential and diversification performance of these energy sources in a context of uncertainty. Accordingly, we, first, show that the connections among the four markets have time-varying characteristics with positive and negative alternating changes in most periods. Random events might cause ephemeral structural changes in correlations. Second, we identify different ways of hedging specific to the energy assets under consideration that provides an efficient risk management framework. Third, we find that the EPU has an asymmetrical and often a positive impact on energy cross-market linkages. Particularly, when macroeconomy facing high uncertainty, then markets become more inseparable. •Exploring the dynamic nexus of energy, clean energy, crude oil, and carbon markets using a DCC-MIDAS specification.•Investigating the asymmetric impact of EPU on cross-asset correlations under different market conditions via the QQ technique.•Comparing the hedging potential and diversification performance of energy assets.•The correlations have time-varying characteristics with positive and negative alternating changes.•The EPU has an asymmetrical and often a positive impact on cross-market linkages.